Mental toughness and resilience in trail runner`s performance - Gameiro, N.; Rodrigues, F.; Antunes, R.; Matos, R.; Amaro, N.; Jacinto, M.; Monteiro, D. (Perceptual and Motor Skills, 2023)
Our purpose with this study was to analyze trail runners` psychological variables of mental toughness (MT) and resilience, and their associations with runners` performances within a quantitative cross-sectional study. In total, we analyzed data from 307 Portuguese trail runners (60 female, 247 male), aged between 20 to 66 years (M age = 41.98; SD = 7.74). The results showed that the measurement model, including the factors of MT, resilience, and performance variables, exhibited an adequate fit to the data: X^2 = 150.01 (74); BS-p = .003; CFI= .953; TLI = .942; RMSEA = .058 90% (.045, .071) and SRMR= .042. Standardized direct effects revealed positive associations between these variables. More specifically: (a) MT was significantly associated with resilience; and (b) resilience was significantly associated with performance. The indirect regression paths showed that MT was positively associated with performance, with resilience considered a possible mediator (ß = .09 IC = .010, .168; p = .02). In total, considering direct and indirect effects, the model explained 21% of performance variance among trail runners.